Pricing Benchmarking for Islamic Banking Products: Application and Impact - Mohammad Qutaiba; Mohd Owais (Islamic Banking and Finance Review, 2025)
Islamic property financing (IPF) in Malaysia has evolved into a well-established system that adheres to Shariah principles while competing with conventional financial models. However, the continued reliance on interest-based benchmarks in pricing remains a challenge. This study critically examines the feasibility of establishing an independent price benchmarking system for (IPF) that ensures profitability while complying with Shariah principles. It explores the implications of using conventional benchmarks, investigates alternative pricing models, and evaluates the impact of displaced IRs on Islamic banks. Various methodologies, including the rate of profit mechanism model, Tobin’s Q theory, and rental-based pricing, are analyzed as potential solutions to replace conventional interest-based benchmarks. The research highlights the necessity of balancing financial sustainability with ethical Islamic banking practices in order to create a more independent and competitive Islamic financial system.